Uncommon Roman Burials from Paneas, Caesarea Philippi - Tchekhanovets, Yana; Bekker-Shamir, Marina; Nagar, Arfa; Nagar, Yossi (Antiguo Oriente, 2026)
The following article presents the results of salvage excavations carried out at the Roman period necropolis of the ancient city of Paneas, Caesarea Philippi, where several sealed and disturbed tombs found empty of osteological remains were studied, alongside two funerary monuments belonging to a type previously unattested in this area. The characteristics of these monuments seem to be inspired by the funerary architecture of the Syrian region.